Ocular complications and factors affecting visual outcome in herpes zoster ophthalmicus: A prospective study in a tertiary care teaching hospital, Telangana, India - Babu Manda,; Porika Ram Mohan Lal, (Asian Journal of Medical Sciences, 2023)
Background: Herpes zoster ophthalmicus (HZO) is caused by varicella zoster virus and affects the ocular branch of the trigeminal nerve. Aims and Objectives: To investigate the ocular complications and factors affecting visual prognosis in patients with HZO, a Varicella zoster virus infection affecting the ocular branch of the trigeminal nerve. Materials and Methods: 40 patients meeting the criteria were enrolled in the study, which was conducted at the Department of Ophthalmology, SVS Medical College, Mahbubnagar, Telangana, India. Results: The study found that more than 50% of HZO patients experienced ocular involvement, and acute corneal lesions, such as punctate and dendriform keratitis, uveitis, and severe post-herpetic discomfort, were associated with lower visual acuity. However, none of the patients in the study experienced posterior segment HZO problems such as acute retinal necrosis or progressive outer retinal necrosis. Older age groups were found to be more likely to experience post-herpetic neuralgia (PHN), which was also associated with nasociliary nerve involvement and vision loss. Conclusion: The study suggests early treatment with tricyclic antidepressants to aid in the early resolution of PHN. In addition, the study aimed to evaluate the effect of HIV/AIDS on ocular complications in HZO patients but did not report any findings in this regard.